Effects of dandelion (Taraxacum sp.,) supplements on lactation performance, antioxidative activity, and plasma metabolome in primiparous dairy cows - Yan Li; Jie Mei; Jiaqi Wang; Hongyun Liu (Animal Bioscience, 2023)
Objective This study evaluated the effects of dandelion supplements on lactation performance, circulating antioxidative activity and plasma metabolomics in primiparous dairy cows. Methods A total of 60 mid-lactation dairy cows (milk yield = 34.29±0.34 kg/d; days in milk = 151.72±2.36 days) were divided into 4 treatment groups randomly, comprising the addition of dandelion at 0, 100, 200, 400 g/d per head. The experiment lasted for 8 weeks with an extra 10 days’ pre-feeding period. Milk and blood samples were collected, and plasma samples were selected to perform metabolomics analysis. Results Supplementing 200 g/d of dandelion increased the yield of milk and lactose (p≤ 0.05). The milk somatic cell counts (p≤0.05) were lower in all dandelion groups than those in the control group. The activity of glutathione peroxidase (p≤0.05) and superoxide dismutase (p≤0.05) were increased and plasma malondialdehyde (p = 0.01) was decreased when cows were fed 200 g/d dandelion. Plasma metabolomics analysis showed that 23 hub differential metabolites were identified in the 200 g/d dandelion group. These metabolites such as ribose, glutamic acid, valine, and phenylalanine were enriched in D-glutamine and D-glutamate metabolism (p = 0.06, impact value = 1), phenylalanine, tyrosine, and tryptophan biosynthesis (p = 0.05, impact value = 0.5), and starch and sucrose metabolism (p = 0.21, impact value = 0.13). Moreover, correlation analysis showed that circulating ribose, mannose, and glutamic acid were positively related to milk yield. Conclusion Dandelion supplementation could improve lactation performance and elevate the plasma carbohydrate and amino acids metabolism and antioxidative activity. Supplementation of 200 g/d dandelion is recommended for lactating dairy cows.